Uncoupling cell division and cytokinesis during germline development in metazoans - Gerhold, Abigail R.; Labbé, Jean-Claude; Singh, Ramya (Frontiers in Cell and Developmental Biology, 2022)
The canonical eukaryotic cell cycle ends with cytokinesis, which physically divides the mother cell in two and allows the cycle to resume in the newly individualized daughter cells. However, during germline development in nearly all metazoans, dividing germ cells undergo incomplete cytokinesis and germ cells stay connected by intercellular bridges which allow the exchange of cytoplasm and organelles between cells. The near ubiquity of incomplete cytokinesis in animal germ lines suggests that this is an ancient feature that is fundamental for the development and function of this tissue. While cytokinesis has been studied for several decades, the mechanisms that enable regulated incomplete cytokinesis in germ cells are only beginning to emerge. Here we review the current knowledge on the regulation of germ cell intercellular bridge formation, focusing on findings made using mouse, Drosophila melanogaster and Caenorhabditis elegans as experimental systems.